Fluorescent Microplastic Uptake by Immune Cells of Atlantic Salmon (Salmo salar L.) - Abihssira-García, Isabel S.; Park, Youngjin; Kiron, Viswanath; Olsvik, Pål A. (Frontiers in Environmental Science, 2020)
The ubiquitous presence of microplastics and their marine ecotoxicity are major public concerns. Microplastics are ingested accidentally by the marine fauna or are taken up indirectly through the food chain. These particles can accumulate in cells and tissues and affect the normal biological functions of organisms, including their defense mechanisms. There is limited information available about the response of immune cells to microplastics; the degree of uptake by the cells, the response of different organs or the impact of environmental concentrations of microplastic are matters that remain unclear. Moreover, very little is known about the toxicity of different polymer types. This study aimed to shed light on the physical impact of small microplastics (1 to 5 µm) on cells from Atlantic salmon. Immune cells from intestine, blood and head kidney were exposed to green fluorescent polyethylene microplastic (PE-MP), yellow fluorescent polystyrene microplastic (PS-MP) and both. High (50 mg/L), medium (5 mg/L) and low (0.05 mg/L) concentrations were tested for 1, 24, 48 and 72 h to study cell mortality and microplastic uptake. Quantitative data of microplastic uptake by fish immune cells were obtained for the first time by imaging flow cytometry. Salmon immune cells showed a relatively low ability to phagocytose microplastics. Less than 6 % of the cells ingested the particles after 48 h of exposure to high concentrations. Cells also phagocytosed microplastics at low concentrations although at low rates (< 0.1 %). PE-MPs was phagocytosed by higher percentage of cells compared to PS-MPs and the former bioaccumulated in time while the latter decreased over time. However, each cell generally phagocytosed more PS-MPs particles than PE-MPs. Cells from different tissues showed different responses to the microplastic polymers. In conclusion, this study shows that immune cells of Atlantic salmon can phagocytose microplastics, and the impact is dependent on the microplastic type. PE-MPs, the most abundant polymer in the oceans and a widely used plastic in salmon aquaculture, was more easily taken up than PS-MPs. Furthermore, the study demonstrates how imaging flow cytometry can be applied in microplastics research.